Nurses’ Knowledge and Attitudes about Adult Post-Operative Pain Assessment and Management: Cross Sectional Study in Qatar - Haya Samara (19757094) (2024)
Background: Pain is a complex and challenging phenomenon. People have different pain experiences, but everyone has the right to effective pain management. Pain assessment and management are integral components of a nurse’s role. Aim: To assess the knowledge and attitudes of nurses in Qatar about adult post-operative patients’ pain assessment and management, and the factors that may be associated with such knowledge and attitudes. Methods: Post-operative registered nurses from all peri-operative areas at Hamad Medical Corporation participated in a cross-sectional online survey using a self-administered questionnaire. A knowledge and attitudes (K&A) score was calculated. Associations between K&A and potential explanatory variables were assessed using t-tests and one-way ANOVA. Results: A total of 151 post-operative nurses participated in the study. The mean knowledge and attitudes (K&A) score was 19.6 ± 4.5 out of 41 (48%), indicating a large deficit in nurses’ knowledge and attitudes about adult post-operative pain. There were no statistically significant differences in the mean K&A scores of participants based on gender, nationality, education level, marital status, workplace facility, current job designation, or hours of pain education. Conclusions: There is a significant deficit in post-operative nurses’ knowledge and attitudes about pain across the nursing workforce in post-operative care. Implications for nursing education and policy: Evidence-based, innovative nursing education courses are needed to improve nurses’ knowledge and attitudes about pain assessment and management. Health service policy is required to ensure that evidence-based in-service education on pain management is compulsory for all nurses. This study was not registered. Other Information Published in: Nursing Reports License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/nursrep14030153